Cross-Sectional and Prospective Associations between Physical Activity and C-Reactive Protein in Males. - Aírton J Rombaldi; Lúcia C Pellanda; Renata M Bielemann; Denise P Gigante; Pedro C Hallal; Bernardo L Horta (PLoS ONE)
Background There is conflicting evidence about the association between physical activity and inflammatory markers. Few prospective studies are available, particularly from low and middle-income countries. This study was aimed at assessing the cross-sectional and prospective associations between physical activity and C-reactive protein (CRP) levels in males belonging to the 1982 Pelotas (Brazil) Birth Cohort Study. Methods The sample comprised 2,213 males followed up at the ages of 18 and 23 years. We performed high sensitivity CRP assays; we used a cut-off of 3 mg/L in categorical analyses. We measured physical activity by self-report at ages 18 and 23 years. Body mass index and waist circumference were studies as possible mediators. Results CRP levels above the 3mg/L cut-off were found in 13.3% (95%CI: 11.7; 14.8) of the individuals. We found no evidence for an association between physical activity (leisure-time or all-domains) and either continuous (geometrical mean) or categorical CRP. We confirmed these null findings in (a) prospective and cross-sectional analyses; (b) trajectories analyses. Conclusions There was no association between CRP levels and physical activity levels in early adulthood in a large birth cohort. Little variability in CRP at this early age is the likely explanation for these null findings.